PERMASALAHAN PENERBITAN SERTIPIKAT BERDASARKAN AKTA JUAL BELI DI KECAMATAN CILINCING, JAKARTA UTARA: Problems Of Issuing Certificates Based On Deeds Of Sale And Purchase In Cilincing District, North Jakarta - Agung Daniel Panogari Simanjuntak; Dinda Keumala (AMICUS CURIAE, 2025)
The transfer of rights through sale and purchase must be evidenced by a Sale and Purchase Deed made by the Land Deed Official (PPAT), which serves as proof of the transfer of rights from the seller to the buyer and for land registration purposes. The identification of the problem in this research is the validity of five Sale and Purchase Deeds made before Slamet Musyianto, S.H., PPAT in North Jakarta Administration City and whether the issuance of five certificates in the name of Aspah Supriadi derived from those deeds in the PTSL program in Cilincing District by the Land Office of North Jakarta Administration City complies with the National Land Law provisions. This research uses a normative type with a descriptive nature. Secondary data was collected through literature study. Analysis was conducted qualitatively with conclusions drawn deductively. Based on the research results and conclusions, it is concluded that the Sale and Purchase Deeds made before the PPAT are invalid because they do not meet the requirements of land sale and purchase under the National Land Law and the criteria for making Sale and Purchase Deeds. Furthermore, the issuance of certificates under the PTSL program does not comply with applicable regulatory provisions.